Lipid peroxidation markers in children with anxiety disorders and their diagnostic implications. (March 2014) - Ceylan, Mehmet Fatih; Guney, Esra; Alisik, Murat; Ergin, Merve; Dinc, Gulser Senses; Goker, Zeynep; Eker, Sevda; Kizilgun, Murat; Erel, Ozcan
<x content-type="archive" xml:space="preserve">Abstract</x> Objective Numerous factors, including genetic, neurobiological, neurochemical, and psychological factors, are thought to be involved in the development of anxiety disorders. The latest findings show that the pathophysiology of anxiety disorders might be associated with oxidative stress and lipid peroxidation; however, no studies have so far investigated lipid peroxidation markers in children with anxiety disorders. Serum levels of lipid hydroperoxide (LOOH) are a reliable marker of lipid peroxidation. Paraoxonase and arylesterase are two enzymes that protect against such peroxidation, and might also be diagnostic markers. In this study, we investigated whether there are associations between anxiety disorders and lipid peroxidation markers in children, and assessed the diagnostic performance of these markers. Methods The study group consisted of 37 patients (children and adolescents) with anxiety disorders. A control group, matched for age and gender, was composed of 36 healthy subjects. Venous blood samples were collected, and LOOH levels and paraoxonase and arylesterase activity were measured. Results LOOH levels were significantly higher in the anxiety disorders group than in the control group. There were no significant differences in paraoxonase or arylesterase activities between the patient and the control groups. Discussion Lipid peroxidation or oxidative damage might play a role in the aetiopathogenesis of anxiety disorders. LOOH may be a potential biological marker for anxiety disorders in children.